Distribution, variability and sources of tropospheric ozone over south China in spring: intensive ozonesonde measurements at five locations and modeling analysis - Zhang, Yiqiang; Liu, Hongyu; Crawford, James H.; Considine, David B.; Chan, Chuenyu; Oltmans, Samuel J.; Thouret, Valerie (American Geophysical Union, 2012)
We examine the characteristics of the spatial distribution and variability of tropospheric ozone (O3) by analysis of 93 ozonesonde profiles obtained at five stations over south China (18–30 N) during a field campaign in April–May 2004. We use a global 3-D chemical transport model (GEOS-Chem) to interpret these characteristics and to quantify the sources of tropospheric O3 over south China during this period. The observed tropospheric O3 mixing ratios showed strong spatiotemporal variability due to a complex interplay of various dynamical and chemical processes. A prominent feature in the upper and middle troposphere (UT/MT) was the frequent occurrence of high O3 mixing ratios shown as tongues extending down from the lower stratosphere or as isolated layers at all stations. The model largely captured the observed pattern of day-to-day variability in tropospheric O3 mixing ratios at all stations, but often underestimated those tongues or isolated layers of O3 enhancements observed in the UT/MT, especially at low-latitude stations. We found that tropospheric O3 along the southeast China coast was mainly produced within Asia. Lightning NOx emissions (over South Asia and equatorial Africa) and/or stratospheric influences were responsible for major events of high O3 observed in the UT/MT at all stations. Underestimated contributions of these sources likely led to the model’s underestimate in the low-latitude UT/MT O3. This study emphasizes the need for improved understanding of lightning NOx emissions and stratospheric influences over the Eurasian and African continents and for better representation of these processes in current global models.